The Relationship Between Exchange Rate and FDI Inflows in Malaysia - Mohd. Jaffri, Abu Bakar (2009)
This paper examines the relationship between exchange rate and FDI inflow in Malaysia. This paper has used Multiple Linear Regressions in order to explore the relationship. This study has analyzed the data on yearly basis ranging from 1997 to 2008. From the results of the regression, the researcher was rejected Ho and accept H1, which indicate that there is a relationship between exchange rate and FDI inflow in Malaysia.